In Vitro Chemoresponse Analysis of Cervical Cancer Patient Specimens. Issue 9 (1st November 2014) - Grigsby, Perry W.; Gan, Christine M.; Tillmanns, Todd D.; Del Priore, Giuseppe
Abstract : Purpose: The objective of this study was to report the results of in vitro chemoresponse analysis of primary, metastatic, and recurrent human cervical cancers. Methods: There were 557 tumor specimens submitted for testing from August 2006 to June 2010. Single agents tested were cisplatin, carboplatin, paclitaxel, docetaxel, epirubicin, fluorouracil, 4-hydroxy ifosfamide (active metabolite of ifosfamide), SN-38 (active metabolite of irinotecan), topotecan, and vinorelbine. Doublets tested were carboplatin/paclitaxel and cisplatin/topotecan. Tumor response was determined from dose-response curves. Results were scored as responsive, intermediate, or nonresponsive. Chemoresponse was reported as the combined responsive and intermediate results. Results: Three hundred fifty-three (63.4%) of 557 submitted specimens were successfully assayed. Confirmation of histology and tumor status (primary, metastatic, or recurrent) was available for 273 specimens. The chemoresponse of the most active agents in primary cancers (n = 151) was 75% for SN-38, 71% for 4-hydroxy ifosfamide, 62% for topotecan, and 73% for carboplatin/paclitaxel. The chemoresponse of metastatic cancers (n = 66) was 54% for SN-38, 51% for 4-hydroxy ifosfamide, 44% for epirubicin, and 53% for carboplatin/paclitaxel. The chemoresponse for recurrent cancers (n = 56) was 44% for epirubicin, 41% for 4-hydroxy ifosfamide, 39% for vinorelbine, 39% for paclitaxel, 36% for topotecan, 46% for carboplatin/paclitaxel, and 35% for cisplatin/topotecan. The overall chemoresponse was greater in primary cancers (58%) than in recurrent cancers (35%) ( P < 0.0001). Conclusions: In vitro chemoresponse analysis of cervical cancer biospecimens is feasible. Chemoresponse results are variable depending on tumor status. Clinical studies of assay-directed therapy should be developed.